Analysis of Sap Fiori Utilization and its Influence on Employee Administrative Processes at Sinarmas Coal Mining Company - Nadia Saidati Salsabila (Journal of Economics and Business UBS, 2026)
The digitalization of talent management is essential to meet the modern workforce's expectations for an intuitive technology experience. This study evaluates the use of SAP Fiori at PT Bumi Kencana Eka Sakti, a coal mining company under Sinarmas, focusing on the gap between technology implementation and user satisfaction. The main objective of this study is to evaluate the effectiveness of SAP Fiori use from an employee perspective and develop UI/UX development recommendations. This study argues that continuous innovation, driven by a user-centered design approach, is a key mediator between SAP Fiori quality and employee retention. This study uses qualitative methods with content analysis. Data will be collected through in-depth interviews and surveys to gain a comprehensive understanding of user perceptions, experiences, and challenges. This study is expected to provide an in-depth evaluation of SAP Fiori's effectiveness, identifying its strengths and areas for development. These findings will form the basis for formulating UI/UX innovation recommendations that can improve user experience, contribute to talent retention, and provide scientific contributions by linking digital innovation with HR management outcomes.